2005
DOI: 10.1074/jbc.m501449200
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of NBS1 Contributes to Transformation through the Activation of Phosphatidylinositol 3-Kinase/Akt

Abstract: Nijmegen breakage syndrome (NBS) is a chromosomal instability syndrome associated with cancer predisposition, radiosensitivity, microcephaly, and growth retardation. The NBS gene product, NBS1 (p95) or nibrin, is a part of the hMre11 complex, a central player associated with double strand break repair. We previously demonstrated that c-Myc directly activates NBS1 expression. Here we have shown that constitutive expression of NBS1 in Rat1a and HeLa cells induces/enhances their transformation. Repression of endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
82
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 37 publications
6
82
0
Order By: Relevance
“…In addition, we showed previously that c-MYC, a dominant oncoprotein, directly activates NBS1 expression and that overexpression of NBS1 increases cell proliferation (31). Our recent results show that overexpression of NBS1 contributes to transformation through the activation of phosphatidylinositol 3-kinase (PI3K)/Akt (32). All these results implicated a role of NBS1 in the process of cell proliferation and tumorigenesis.…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…In addition, we showed previously that c-MYC, a dominant oncoprotein, directly activates NBS1 expression and that overexpression of NBS1 increases cell proliferation (31). Our recent results show that overexpression of NBS1 contributes to transformation through the activation of phosphatidylinositol 3-kinase (PI3K)/Akt (32). All these results implicated a role of NBS1 in the process of cell proliferation and tumorigenesis.…”
mentioning
confidence: 68%
“…Real-time PCR analysis was done using 1 Ag total RNA isolated from tumor and neighboring normal tissues. Quantitative real-time PCR was done in a PRISM ABI7700 Sequence Detection System (Applied Biosystems, Foster City, CA) with the preset PCR program, and TBP (TATA box binding protein) was selected as an internal control (32). The primer sequences used in real-time PCR were NBS1 5V -ATGGAGGCCATATTTCCATGAC-3V and 5V -CAAGCAGCCA-GAACTTGGAAG-3V and TBP 5V -TGGTGGTGTTGTGAGAAGATGG-3V and 5V -CGGTGGGCACTTACAGAAGG-3V .…”
Section: Methodsmentioning
confidence: 99%
“…Increased NBS1 expression has been observed in non-small cell lung carcinoma, hepatoma, melanoma and esophageal cancer samples. [36][37][38] Furthermore, Chen et al 36 have recently demonstrated that constitutive expression of NBS1 in Rat1a and HeLa cells induces/enhances their transformation through stimulation of phosphatidylinositol (PI)3-kinase activity, leading to increased phosphorylation levels of Akt and its downstream targets such as mammalian target of rapamycin. It is thus tempting to speculate that increased NBS1 expression contributes to TCL1-induced enhanced Akt signaling in T-PLL cells, which has been suggested to be causal for disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially important, this set of genes included NBS1 or nibrin, the overexpression of which has T-cell prolymphocytic leukemia J Dürig et al recently been shown to contribute to the oncogenic transformation of head and neck cancer and non-small cell lung cancer cells through the activation of the PI3/Akt pathway. [36][37][38] Furthermore, chromosome 8 aberrations were associated with aberrant expression of the erythrocytic structural membrane protein ankyrin-1, which was absent in the eight normal control samples and the T-PLL case lacking iso(8q) (see T-PLL 3 in Figure 4). Aberrant expression of ankyrin-1 was confirmed at the protein level using western blot ( Figure 5).…”
Section: T-cell Prolymphocytic Leukemiamentioning
confidence: 97%
“…Studies in mice have indicated that heterozygous for NBS1-null mutations develop tumors in lung, liver, mammary gland and prostate (Dumon-Jones et al, 2003;Zhang et al, 2006). NBS1 overexpression has been observed in several smoking-related cancer sites including NSCLC, hepatoma, esophageal cancer and head and neck squamous cell carcinoma (HNSCC) (Chen, 2005;Yang, 2006). Furthermore, it was also correlated with recurrence/ metastasis of oral squamous cell carcinoma and the poor prognosis of HNSCC (Yang, 2006;Hsu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%